2015
DOI: 10.2174/0929867322666150818103624
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility as a Strategy in Nucleoside Antiviral Drug Design

Abstract: As far back as Melville Wolfrom's acyclic sugar synthesis in the 1960's, synthesis of flexible nucleoside analogues have been an area of interest. This concept, however, went against years of enzyme-substrate binding theory. Hence, acyclic methodology in antiviral drug design did not take off until the discovery and subsequent FDA approval of such analogues as Acyclovir and Tenofovir. More recently, the observation that flexible nucleosides could overcome drug resistance spawned a renewed interest in the field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…It was then found that fleximers can bind to atypical enzymes and that they can overcome point mutations, which usually confer resistance to the rigid nucleoside analogue. 183 Further, broad-spectrum antiviral activity may be achieved through the fleximers’ ability to take part in “mutually induced fit”. 182 Combining the split purine base with an acyclic glycon (as found in the anti-herpesvirus drug acyclovir) has led to promising activity against members of different RNA virus families, including Filo -, Flavi-, and Coronaviridae .…”
Section: Targeting Viral Rna Synthesis With Direct-acting Antiviral Nmentioning
confidence: 99%
“…It was then found that fleximers can bind to atypical enzymes and that they can overcome point mutations, which usually confer resistance to the rigid nucleoside analogue. 183 Further, broad-spectrum antiviral activity may be achieved through the fleximers’ ability to take part in “mutually induced fit”. 182 Combining the split purine base with an acyclic glycon (as found in the anti-herpesvirus drug acyclovir) has led to promising activity against members of different RNA virus families, including Filo -, Flavi-, and Coronaviridae .…”
Section: Targeting Viral Rna Synthesis With Direct-acting Antiviral Nmentioning
confidence: 99%
“…Efforts are globally underway to create an efficient vaccine or drug for prevention or treatment of the SARS infection (31)(32)(33). In this context, many reports showed that Mpro is an ideal target for drug design and development (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…Reports on in vivo and in vitro applications of LPV in SARS treatment provided evidence that LPV and RTV may improve the Ribavarin effect on SARS infections in a dose dependent manner and reduce the death rate by about 20% -30% (43,44). Also, NFV, an anti HIV-1 protease, showed to prevent coronavirus replication and limit its cytotoxic effect on host cells (31)(32)(33)44). …”
mentioning
confidence: 99%
“…Another structural modification which has proven effective was the development of the fleximers – nucleoside analogues wherein the purine base has been split into two separate heterocyclic fragments but remains connected by a single C-C bond ( Seley et al, 2002 ; Seley et al, 2005 ; Peters H. et al, 2015 ; Ku and Seley-Radtke, 2018 ). Thus, the fleximers exhibit additional conformational freedom in order to maximize structural interactions in the active site of the target enzyme while maintaining the structural similarity with a normal nucleoside substrate or inhibitor necessary for recognition by the enzyme ( Seley et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%